"A New Spelling of My Name": Becoming a (Black, Feminist, Immigrant) Autoethnographer Through Zami. (April 2020) - Burkhard, Tanja
In this article, I provide the historical context for the reception of Audre Lorde's biomythography Zami's by Black women across the African diaspora as a backdrop for my own autoethnographic engagement of the book. I narrate my journey to claiming space within the field of autoethnography by anchoring my discussion in Zami and its themes. The goal of this work is to illustrate the crucial nature of autoethnographic work to transnational Black feminism, and its ongoing importance to women from and in marginalized communities.